2017
DOI: 10.3389/fpsyg.2017.00636
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Mechanism in Learning Ambiguous Words in a Second Language

Abstract: Ambiguous words are hard to learn, yet little is known about what causes this difficulty. The current study aimed to investigate the relationship between the representations of new and prior meanings of ambiguous words in second language (L2) learning, and to explore the function of inhibitory control on L2 ambiguous word learning at the initial stage of learning. During a 4-day learning phase, Chinese–English bilinguals learned 30 novel English words for 30 min per day using bilingual flashcards. Half of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…To date, the translation‐ambiguity disadvantage has mostly been documented for same‐script materials, such that the to‐be‐learned words used the same orthographic system (e.g., Dutch–English and German–English). Notably, the results of a recent study testing the learning of new meanings of known foreign language words indicated that the translation‐ambiguity disadvantage may be present across scripts (Lu, Wu, Dunlap, & Chen, ; see also Fang, Perfetti, & Stafura, ; Rodd et al., ). In particular, Lu et al.…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…To date, the translation‐ambiguity disadvantage has mostly been documented for same‐script materials, such that the to‐be‐learned words used the same orthographic system (e.g., Dutch–English and German–English). Notably, the results of a recent study testing the learning of new meanings of known foreign language words indicated that the translation‐ambiguity disadvantage may be present across scripts (Lu, Wu, Dunlap, & Chen, ; see also Fang, Perfetti, & Stafura, ; Rodd et al., ). In particular, Lu et al.…”
Section: Background Literaturementioning
confidence: 99%
“…In particular, Lu et al. () taught native Chinese speakers ambiguous and unambiguous English pseudowords, withholding the presentation of the second meaning of the ambiguous words until the second session (see also Degani et al., ). The to‐be‐learned English pseudowords were presented visually along with their meaning (depicted in Chinese characters).…”
Section: Background Literaturementioning
confidence: 99%
“…However, L2 word acquisition includes multiple facets—not only learning novel word form and meaning but also learning additional meanings of already-learned words ( Bogaards, 2001 ). A study using a sequential learning paradigm to investigate the learning of novel ambiguous L2 words found that the later-learned meaning representation is weaker than the first-learned one ( Lu et al, 2017 ), which might be due to interference from the unrelated first-learned meaning; other studies have found that the activation of original meanings during the encoding of new meanings produces an interaction between new and existing word knowledge, a process that may facilitate the integration of new information ( van Kesteren et al, 2012 ; Atir-Sharon et al, 2015 ; Schlichting et al, 2015 ). However, the studies mentioned above were focused on the learning of novel words (e.g., Atir-Sharon et al, 2015 ; Bracken et al, 2017 ; Lu et al, 2017 ), which is different from learning new meanings for familiar words.…”
Section: Introductionmentioning
confidence: 99%
“…A study using a sequential learning paradigm to investigate the learning of novel ambiguous L2 words found that the later-learned meaning representation is weaker than the first-learned one ( Lu et al, 2017 ), which might be due to interference from the unrelated first-learned meaning; other studies have found that the activation of original meanings during the encoding of new meanings produces an interaction between new and existing word knowledge, a process that may facilitate the integration of new information ( van Kesteren et al, 2012 ; Atir-Sharon et al, 2015 ; Schlichting et al, 2015 ). However, the studies mentioned above were focused on the learning of novel words (e.g., Atir-Sharon et al, 2015 ; Bracken et al, 2017 ; Lu et al, 2017 ), which is different from learning new meanings for familiar words. In the case of learning new ambiguous L2 words, neither the lexical formal representation nor the multiple semantic representation(s) have been well established during the learning process, meaning that this case cannot provide information about how the stable representation of previously known meanings influences the learning of new meanings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation